Disembodied Language in Early-Onset Schizophrenia - Zakowicz, Przemysław; Skibińska, Maria; Pawlak, Joanna (Frontiers in Psychiatry, 2022)
Recent view on schizophrenia phenomenology underlines the impaired relations between mind and the body. An aberrant feeling of ipseity may be the real source of suffering for psychotic patients and impacts general symptomatology. The disturbed connection between thinking processes and environmental stimuli may lead to language disembodiment. In the study we aimed to experimentally test the presence of disembodied language and investigate its association with symptoms of psychosis in adolescents diagnosed with early-onset schizophrenia spectrum disorders. Assessment of language embodiment was conducted using the author’s test (Zabór Verbal Task, ZVT) with concurrent linguistic and clinical assessment using Thought, Language and Communication Scale (TLCS) and Positive and Negative Symptoms Scale (PANSS). The study group of patients (n=31) aged 11-18 years, with diagnosis of schizophrenia-spectrum according to DSM-IV and ICD-10 criteria was compared with sex and age-matched healthy control sample (n=31). Psychotic patients made more errors in ZVT than healthy controls (p=0.01) and this parameter did not improve after 6 to 8 weeks standard treatment (p=0.55). Higher number of errors in ZVT were associated with presence of auditory hallucinations (OR 1.14; 95% CI 1.02-1.26). ZVT errors coincided with perception disorders, alternatively to TLCS score where we observed association with abnormal beliefs. The results of this preliminary studies indicate value of phenomenological approach in diagnosis of schizophrenia-spectrum and suggest potential involvement of language disembodiment in symptomatology.